Second Five-Year Plan Programme for 1957-58 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1957)
The outlay during the Second Year of the Second Plan was fixed at Rs. 34 crores after discussions with the team of Officers from the Planning Commission and the Central Ministries, in January 1957. Subsequent to that, the provisions earmarked for each scheme had to be slightly altered in view of the changes suggested by the Central Ministries, when schemes, for which Central assistance was expected, were sent up to them for their acceptance and in view of the changes proposed by the various Departments subject to the ceilings fixed for each head of development.
Planning and Development Department, Government of Andhra Pradesh